You are on page 1of 2

Exercícios:

( ) (
1)y = cot g x 3 + 3 sec )
x +1

2)y = x 2 . cos sec (5 x )

(
3)y = cotg3 3x 5 + 1 )
4)y = sen(8x + 3 )

5)y = tg3 5 − 6x

(
6)y = cos 3x 5 − 5x 3 )
(
7)y = tg 8 x − 5 x )
sen x
8 )y =
1 + cos x

sec 2x
9 )y =
tg2x − 1

10) y = sec x.tg( x 2 + 1)

1
11) y =
cos x . cotg x

1 + sec x
12) y =
tg(3x - 1) + sen 2 x

13) y = 2 x cot g x + x 2 tg x
14) y = sen(− x ) + cos(− x )

15) y = (sen (4x ) + cos (2x ))


2

x + cos 3x
16) y =
sen 2x

17) y = (x 2 − 1) tg x - x sen 2x

18) y = tg (- 2x )(x 2 − 2x + 1)

19) y = cos sec 5x . tg x

(
20) y = cos 2 x 2 − 2 x + 1 )

21) (sen x + cos 3x )


3